Effect of Airborne Cloud Seeding on Precipitation through Ensemble Numerical Modeling in the Yeongdong Region of Korea: Effect of Airborne Cloud Seeding on Precipitation through Ensemble Numerical Modeling in the Yeongdong Region of Korea - Chae, Sanghee; Lee, Yong Hee; Chang, Ki-Ho; Koo, Hae Jung; Ro, Yonghun; Hwang, Hyun Jun; Im, Yunkyu; Kim, Bu-Yo; Belorid, Miloslav (Asia-Pacific journal of atmospheric sciences, 2025)
In this study, the effects of cloud seeding experiments were analyzed using ensemble numerical modeling. This study focuses on an aircraft seeding experiment conducted over the East Sea near the Yeongdong region of Gangwon Province on October 4, 2022. The weather research and forecasting (WRF) model was applied with parameterization to reflect the effects of hygroscopic seeding materials. The particle size distribution of domestically produced sodium chloride (NaCl) powder was measured and incorporated into the model. Fifty ensemble members (seeding start time legs) were constructed to calculate the probability of seeding-induced precipitation, which was then used to analyze the precipitation efficiency. The results showed that seeding materials were primarily dispersed to the Yeongdong and Yeongseo regions of Gangwon Province due to northeasterly winds. The 6-h (14:00–20:00 KST) cumulative simulated precipitation enhancement was 2.7, 4.4, and 0.9 mm at Bukgangneung (BGN), Gangneungseongsan (GNSS), and Daegwallyeong (DGY), respectively. Analysis of the precipitation ion components confirmed a distinct increase in seeding material-related ions at the BGN site, corresponding to 98% probability of seeding-induced precipitation, as per ensemble-based analysis. Areas with a high probability of seeding-induced precipitation exhibited increased precipitation, with an efficiency of 19.63% (median) and 23.50% (mean) in the 100% probability zones. The highest precipitation efficiency occurred at altitudes of 1000–1200 m above sea level, aligning with the seeding altitude (approximately 1.5 km above sea level) and cloud formation height.